Gastric metastasis of primary testicular mixed germ cell tumor: a case report - Barreda Bolaños, Fernando (2022)
Testicular cancer is the most common solid tumor in men between ages 15 and 29. It can metastasize through the hematogenous or lymphatic routes to different organs such as the lung and liver (common) and the stomach (uncommon). We present thecase of a 30-year-old male patient with upper gastrointestinal bleeding due to two ulcers in the stomach body with histology of unspecified small-cell malignant neoplasm. CT scans showed a right testicular tumor with secondary implants in the brain, lung, liver and spleen. β-HCG (35,5354 mIU/mL), AFP (500 ng/mL) and LDH (1,669 IU/L) tests were conducted. A right radicalorchiectomy was performed. It is concluded that this was a clinical stage IIIC primary germ cell tumor of the right testis due to liver, spleen, lung, gastric and brain metastases.